An Overview of Digital Library Implementation in Cambodian High Schools: A Case Study of a New Generation School (NGS) in Phnom Penh - Pol, Thou (International Journal of Language and Literary Studies, 2025)
The innovation of Education 4.0 has rapidly transformed the educational environment through the growth of technology including digital library management (DLM). However, most libraries in Cambodian high schools are not yet ready for this conversion. This study aimed to discover the digital library (DL) engagement in a New Generation High School (NGS) in Phnom Penh. It was carried out A case study mixed-methods design using structural equation modelling (SEM) observation and semi-structured interviews. The findings indicated that some digital platforms have been used in the library and performed various advantages such as enhancing connection and communication (Social media and Google Forms & Spreadsheet), improving accessibility (Library Management System (LMS) and Microsoft Office and Google Workspace), increasing efficiency and simplicity (Auto processes), data-driven decision making (Google Forms & Spreadsheet integration), cost-effectiveness (free & cloud-based solution; Google), and enhancing user experience (user-friendly interface like social media and LMS). The librarians also stressed that English literacy, information communication technology (ICT) literacy and operation budget are the concerns of applying digital libraries in high school. Larger sample sizes of both NGSs and general high schools are highly recommended for further research across the country.